2014
DOI: 10.1136/bmjopen-2013-004376
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in idiopathic intracranial hypertension: a prospective case–control study

Abstract: ObjectiveTo explore the extent and nature of cognitive deficits in patients with idiopathic intracranial hypertension (IIH) at the time of diagnosis and after 3 months of treatment.DesignProspective case–control study.SettingNeurological department, ophthalmological department and a tertiary headache referral clinic at a Danish university hospital.Participants31 patients with definite IIH referred from June 2011 to February 2013 and included within 1 week of diagnostic intracranial pressure (ICP) measurement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 32 publications
9
77
1
5
Order By: Relevance
“…In the IIHTT QOL scores were measured and found to be reduced at the time of the IIH diagnosis 75. PMD in the best eye, visual acuity in the worst eye, visual symptoms, and pain symptoms, but not obesity, were independently associated with reduced QOL.…”
Section: Assessment and Investigationsmentioning
confidence: 99%
“…In the IIHTT QOL scores were measured and found to be reduced at the time of the IIH diagnosis 75. PMD in the best eye, visual acuity in the worst eye, visual symptoms, and pain symptoms, but not obesity, were independently associated with reduced QOL.…”
Section: Assessment and Investigationsmentioning
confidence: 99%
“…Other symptoms and clinical signs include dizziness, nausea, reduced memory and concentration and horizontal diplopia due to sixth nerve palsy [Carta et al 2004;Mollan et al 2014;Yri and Jensen, 2015;Yri et al 2012]. Recent studies demonstrated a marked cognitive dysfunction [Kharkar et al 2011;Yri et al 2014a;Zur et al 2015] and indicated that impaired executive function, working memory, processing speed and reaction time remained after normalization of ICP and alleviation of the headache and the visual symptoms [Yri et al 2014a]. It is likely that such cognitive dysfunction could contribute to the substantial loss of work capacity and life quality in patients with IIH and increased focus of the underlying pathophysiology and of their rehabilitation are highly relevant.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Several series regarding patients with IIH have reported cognitive dysfunction associated with a lower NEI-VFQ-25 composite score and NeuroOphthalmic Supplement score. 31 It may be that symptoms of cognitive dysfunction also contribute to a lower QOL.…”
mentioning
confidence: 99%